The Mindful Measurement of Food: Quantification, the Food Pyramid and Discourses of Taste - Mudry, Jessica (Material Culture Review, 2009)
National food guides, food packages and labels and myriad diet books encourage their readers and eaters to count what they eat. The modern pantry is filled with numbers, quantities and claims of “more” and “less.” At the root of these messages is a discourse of quantification that encourages a unique, objective and rational approach to food and eating. In this paper I trouble the reliance on this discourse by American federal nutrition policy-makers. Herein, I point to the underpinnings and emergence of a discourse of quantification of food, I ask how public policies in the form of food guides encourage such a discourse, and I point to more subjective and qualitative discourses that are lost or rendered powerless in the face of quantified food. Résumé Les guides alimentaires, les emballages, les étiquettes et les myriades de livres de régime incitent les consommateurs à se focaliser sur les aspects quantitatifs de ce qu’ils mangent. Le garde-manger moderne est rempli de chiffres, de quantités et de slogans de “plus” et “moins”. À la base de ces messages réside un discours de quantification qui aborde l’alimentation sous un angle scientifique, objectif et rationnel. Cette recherche vise à expliquer pourquoi les politiques alimentaires officielles des États-Unis utilisent uniquement ce discours et à rechercher les fondements de ce dernier. J’interroge les guides alimentaires pour comprendre pourquoi ils amènent les gens à ne considérer que les chiffres en perdant de vue les aspects subjectifs et qualitatifs de la nourriture.